Communicative-Semantic Peculiarities of Tautological Constructions in the Present Indefinite Tense - Chubaryan, Astghik; Mesropyan, Artur (Armenian Folia Anglistika, 2015)
Tautological constructions are widely used in written and oral speech and are expressed in different tenses. Tautologies used in the Present Indefinite tense have their semantic and communicative peculiarities. They outnumber those used in other tenses and are applied to convey different communicative and semantic purport. These meanings largely depend on textual and cultural context, number of the noun, definite and indefinite articles, other interlinguistic and extralinguistic factors. These tautologies may be divided into several groups: those of Tolerance, Obligation, and Tautologies that see through superficial differences. The paper reveals how far the grammatical structure is determined by discourse structure and the speaker’s/writer’s communicative intention.
Keywords: tautological construction; contextual dependence; syntactic formula; semantic peculiarities; communicative charge